Decentralization of Religious Discourse in the Covid times: A Case Study on Hong Kong’s #DeltaΔMovement - Rachel Lai (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2023)
Traditionally, most of Christian religious discourse in Hong Kong has been centralized in established institutions, such as churches and seminaries. However, with the changing times of Hong Kong’s protests in 2019 and the COVID-19 pandemic, young believers have turned to social media to engage in religious discourse under the hashtag “DeltaΔMovement”. This paper will investigate in what ways #DeltaΔMovement has allowed young people to engage in discourse in a decentralized manner, how established institutions are responding to the movement, and insights as to how people may generalize the process of decentralization in various facets of social justice issues, amplifying the voices of the traditionally overlooked and marginalized.